Titanium nitride sensor for selective NO2 detection - Xuefei Zhao; Zhihang Xu; Zhaorui Zhang; Jiahao Liu; Xiaohui Yan; Ye Zhu; J. Paul Attfield; Minghui Yang (Nature Communications)
Abstract Efficient detection methods are needed to monitor nitrogen dioxide (NO2), a major NOx pollutant from fossil fuel combustion that poses significant threats to both ecology and human health. Current NO2 detection technologies face limitations in stability and selectivity. Here, we present a transition metal nitride sensor that exhibits exceptional selectivity for NO2, demonstrating a sensitivity 30 times greater than that of the strongest interfering gas, NO. The sensor maintains stability over 6 months and does not utilize platinum or other precious metals. This notable performance has been achieved through preparation of highly active titanium nitride (TiNx) nanoparticles with exceptionally large surface area and a high concentration of nitrogen vacancies. By contrast, a commercial sample of TiN shows no gas sensing activity. Such devices are potentially scalable for everyday NO2 detection and demonstrate that robust high-performance gas sensors based on inexpensive metal nitrides without precious metals are leading candidates for environmental monitoring technologies.